Age-dependent ACE2/TMPRSS2 expression and SARS-CoV-2 household transmission in Gran Canaria. - Jesús Poch-Páez; Yeray Nóvoa-Medina; Abián Montesdeoca-Melián; Araceli Hernández-Betancor; Francisco J Rodríguez-Esparragón; Svetlana Pavlovic-Nesic; Melisa Hernández-Febles; Jesús M González-Martín; Laura Cappiello; Valewska Wallis-Gómez; Joaquin Quiralte-Castillo; Alejandro Maján-Rodríguez; et al. (PLoS ONE)
Background This study aimed to assess whether the expression of ACE2 and TMPRSS2 is associated with susceptibility to and severity of COVID-19 across age groups. We also evaluated the role of children in household transmission of SARS-CoV-2. Methods We conducted a cross-sectional observational study including 258 households in Gran Canaria between March 10 and June 2, 2020. A total of 650 individuals (including 89 children under 18 years of age) were evaluated using a combined serological testing strategy to confirm past SARS-CoV-2 infection. Gene expression of ACE2 and TMPRSS2 was quantified from saliva samples. Demographic, clinical, and household exposure data were collected for analysis. Results The combined serological approach increased diagnostic sensitivity by 10%. Antibody levels decreased with age in children but increased with age and disease severity in adults. ACE2 expression was slightly elevated in younger children; however, after correction for multiple comparisons, there was no statistically significant association between ACE2 expression and age, antibody titers, or symptom severity.. TMPRSS2 expression did not correlate with any studied variable. Children were less frequently infected (OR = 0.56), and when infected, they experienced milder symptoms and reduced disease severity. Risk factors for transmission included older age and sharing a bedroom with the index case. In adults, risk increased with age; in children, younger age was associated with higher transmission risk. Conclusions Our findings do not support a strong relationship between ACE2 or TMPRSS2 expression levels and susceptibility to or severity of COVID-19. Children appear to be less susceptible to SARS-CoV-2 infection and tend to experience a milder disease course.